2011
DOI: 10.1055/s-0031-1299970
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure Lowering Effect of an Olive Leaf Extract {Olea europaed) in L-NAME Induced Hypertension in Rats

Abstract: A specially prepared olive leaf extract (EFLA 943) has been tested for its blood pressure lowering activity in rats rendered hypertensive by daily oral doses of L-NAME (NG-nitro-L-arginine methyl ester, 50 mg/kg) for at least 4 weeks. Oral administration of the extract at different dose levels at the same time as L-NAME for a period of 8 weeks showed a dose dependent prophylactic effect against the rise in blood pressure induced by L-NAME, best effects being induced by a dose of 100 mg/kg of the extract. In ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
92
1
7

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(112 citation statements)
references
References 21 publications
4
92
1
7
Order By: Relevance
“…Olive leaf contains triterpenes (oleanolic, ursolic, and maslinic acid), flavonoids (luteolin, apigenin, and quercetin), caffeic acid, and tannins [167]. Experimental animal studies on different total olive leaf extract or their constituents have demonstrated hypoglycemic [168], hypotensive [169], nephroprotective [165], antiatherosclerotic [170], antitumor [171] and anti-inflammatory activity [172].…”
Section: Olive Tree (Olea Europaea)mentioning
confidence: 99%
“…Olive leaf contains triterpenes (oleanolic, ursolic, and maslinic acid), flavonoids (luteolin, apigenin, and quercetin), caffeic acid, and tannins [167]. Experimental animal studies on different total olive leaf extract or their constituents have demonstrated hypoglycemic [168], hypotensive [169], nephroprotective [165], antiatherosclerotic [170], antitumor [171] and anti-inflammatory activity [172].…”
Section: Olive Tree (Olea Europaea)mentioning
confidence: 99%
“…This ability to lower blood pressure may justify the traditional use of olive leaf in the treatment of mild to moderate hypertension. However, human studies are needed to clearly establish olive leaf as a potential treatment for high blood pressure [42]. With this respect, a prophylactic blood pressure lowers and cholesterol lowers actions of the olive leaf extract EFLA ® 943 in human was studied by Perrinjaquet-Moccetti et al [38].…”
Section: Olive Leaf Extract and High Blood Pressurementioning
confidence: 99%
“…It is a phenolic compound which has been shown to possess diverse healing properties for its vasodilatory [1], hypotensive [2,3], anti-inflamatory [4], antirheumatic [5], diuretic [6], anti-atherogenic [7] and antipyretic [8] effects. Most of these pharmacologic features of oleuropein ( Figure 1) are due to its potent antioxidant action [9].…”
Section: Introductionmentioning
confidence: 99%
“…The leaves have been used up as a dietary component, in the form of an extract or a whole powder (Karakaya, 2009) Olive leaves have many pharmaceutical properties because of many potentially bioactive compounds that may have anti-hypertensive, antioxidant, hypoglycaemic, anti-inflammatory and hypocholesterolemic properties (Karakaya, 2009). Besides these features, many reports indicated that olive leaves can decrease blood pressure and arrhythmia, increase blood flow in the coronary arteries, decrease and prevent intestinal muscle spasms (Khayyal et al, 2002;Zarzuelo, 1991, Samuelsson, 1951Pereira et al, 2007).…”
Section: Introductionmentioning
confidence: 99%